PELAKSANAAN PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) DENGAN JAMINAN HAK TANGGUNGAN PADA PT. BANK PANIN Tbk. KANTOR CABANG UTAMA (KCU) SOLO - , Vidia Cherria Chairunisa, Dr. Ari Hernawan, S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Objective of this research was to identify types of default in home ownership credit (CRO) with mortgage security in Panin (limited) Branch Solo done by customers and resolution the bank do when its customer default. This is empirical research, added with literary research. Data was analyzed qualitatively. Result of analysis was presented descriptively. Result of the research indicated, first, type of default in home ownership credit (CRO) with mortgage security in Panin (limited) Branch Solo done by customer is not make payment based on the credit contract at determined time, deviation of credit usage, debtor give untrue data/information/statement in the credit contract, debtor violate stipulation determined in Article 10 of the credit contract such as receiving credit from other bank or third party, change business type, rent/transfer goods used as collateral, debtor did not used credit facility in one month. Second, Panin (limited) Branch Solo solve the default case in peaceful negotiation, underhand sale of mortgage object, and auction sale through Bureau of State Receivable and Auction (BUPLN).